PENINGKATAN KAPASITAS PEMBIBITAN Trigona sp. DAN ADOPSI TEKNOLOGI OLEH PETERNAK: UPAYA PENGUATAN PRODUK UNGGULAN DAERAH LOMBOK UTARA - Muhammad Muhsinin; Maskur Maskur; Tapaul Rozi; Lalu Moh. Kasip; Erwan Erwan (Universitas Mataram, 2026)
The development of Trigona sp. bee breeding is a strategic effort to enhance the quality and quantity of honey production in North Lombok Regency, West Nusa Tenggara. Trigona sp. honey, known for its high antioxidant, antibacterial, and nutritional content, has great potential as a regional superior product that can provide health benefits. However, the utilization of Trigona sp. bees in this area remains limited, especially regarding effective breeding techniques and optimal colony management. This community service program aims to provide training and mentoring to local beekeepers on proper and effective Trigona sp. bee breeding techniques. The results of this activity show that 100% of beekeepers participated in the socialization with high enthusiasm, leading to an increased understanding of the potential of Trigona sp. bees in a short period. Furthermore, 90% of participants successfully carried out independent breeding with an 80% success rate, and 75% of beekeepers overcame colony disease issues, contributing to a 25% increase in honey productivity. This program also increased the number of successfully bred colonies by 30%. In addition to improving technical skills, the development of Trigona sp. honey products opens up wider market opportunities and can increase the beekeepers' income. With a practical and participatory approach, this training is expected to improve community welfare and strengthen food security and regional economy in the long term, having a positive impact on the sustainability of natural resource management and the development of local products, while also creating new business opportunities.